PENGARUH JENIS SUBSTRAT YANG BERBEDA TERHADAP SINTASAN DAN PERTUMBUHAN LOBSTER AIR TAWAR (Cherax quadricarinatus - Beny Setiyo Budi; Andi Rahmad R Rahim; Muh. Sulaiman Dadiono (Universitas Muhammadiyah Gresik, 2019)
The existence of freshwater crayfish in Indonesia is not well known among the community, even some people think that this type of lobster can only be obtained from catches. Freshwater lobster cultivators are always faced with the classic problem of low survival, especially during seed stages. The role of the water bottom substrate for freshwater crayfish is to support stabilizing water quality (temperature, pH, dissolved oxygen and ammonia levels). If the substrate condition of the habitat is not suitable, it can inhibit growth and even death. The purpose of this study is; to find out the effect of different basic substrates can increase the survival and growth of freshwater lobsters. The research method used a Completely Randomized Design (CRD) with 4 treatments 3 replications and 1 control. Each container is stocked with 2-inch lobster seeds with a density of 10 heads / container. The substrate application for each treatment is: A = Control, B = Land, C = Sand Malang, and D = Gravel. Based on the results of the research that has been done, it can be concluded that the administration of different substrates only shows significant differences in the survival variable, with the highest number of 96,67% in treatment C (Malang sand) and the lowest with 66,00% in treatment A (Control). While the variables of absolute weight, absolute length, and daily growth rate did not show significant differences in all treatments.